Analysis of Educational Marketing Strategies Through Social Media to Increase New Student Interest - Dian Ardiansah (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
The development of information technology has changed many aspects of life, including education. One significant impact is the use of social media and websites as the primary means of marketing various educational programs. Although MTS N 2 Pangandaran already has various accounts on various social media platforms such as Facebook with the account name "MTsN 2 Pangandaran" with 1248 followers, Instagram with the account name "mtsn2pangandaran" with 1749 followers, TikTok with the account name "mtsn2pangandaran" with 673 followers and the website "mtsn2pangandaran.sch.id", its implementation in social media-based marketing strategies is still considered less than optimal. This is evidenced by the decline in the number of new students from 125 students in 2022, 118 students in 2023, and 110 students in 2024. The problem formulation in this thesis is how social media and website-based marketing strategies can increase the interest of new students at MTS N 2 Pangandaran. The research conducted at MTS N 2 Pangandaran aims to analyze how social media and website-based marketing strategies can increase the interest of new students at MTS N 2 Pangandaran. The type of research used is qualitative research. Data collection techniques used include observation, interviews, and documentation. Meanwhile, to analyze the data obtained, The author conducted the research by collecting all data, reducing data, presenting data, and verifying data. The results of the study, which refer to Philip Kotler's 4P marketing mix theory, show that the marketing strategy for educational products offered by MTsN 2 Pangandaran is considered adequate, based on appearance, photos, videos, pamphlets, live and live streaming. The marketing financing strategy implemented by MTs N 2 Pangandaran has not been well organized, as evidenced by the absence of specific financing details in product marketing.